Influence of particle size of support on reforming activity and selectivity of activated carbon supported platinum catalyst in APR - Meryemoglu, Bahar; Irmak, Sibel; Hasanoglu, Arif; Erbatur, Oktay; Özsel Kaya, Burçak (Elsevier Sci Ltd, 2014)
The aqueous-phase reforming (APR) of biomass-derived compounds has been considered as a promising way to produce hydrogen and developing active reforming catalysts for this process is the challenging issue. The current research was conducted to determine the effect of particle size of support on activity and hydrogen selectivity of activated carbon supported platinum catalyst for APR of glucose, biomass-derived model compound. The commercial activated carbon material was pounded and fractionated based on particle size using 60, 80 and 170 mesh sieves. The activated carbon supported Pt catalysts were prepared by deposition of Pt metals on those fractions by incipient wetness impregnation method. The results showed that although Pt particles deposited on the pounded supports were same size, smaller-sized activated carbon supported Pt catalyst exhibited higher activity and hydrogen selectivity. The performance of the catalyst was better when narrower size distribution of the support particles was used. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Supported Pt catalyst; Activated carbon; Particle size; APR; Glucose